111-3s=63

Simple and best practice solution for 111-3s=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 111-3s=63 equation:


Simplifying
111 + -3s = 63

Solving
111 + -3s = 63

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-111' to each side of the equation.
111 + -111 + -3s = 63 + -111

Combine like terms: 111 + -111 = 0
0 + -3s = 63 + -111
-3s = 63 + -111

Combine like terms: 63 + -111 = -48
-3s = -48

Divide each side by '-3'.
s = 16

Simplifying
s = 16

See similar equations:

| 15(z+406)=240 | | n^2+n-1=5 | | 56=8(c-91) | | 20=-b/.2 | | 8=3(x-1)-(x-7) | | 21-4b=13 | | K+3=11 | | 3(2x-2)-3=3(x-4)+30 | | 9(j+5)=99 | | 4/5v=28 | | 6x-(8x+7)=6x-15 | | 25x+63=13x-65 | | 5y-11=44 | | 3+3d=12 | | 3=9-2r | | 3(x-1)+4=2x | | P-4=1+3p+3p | | cos^2x+sin^2x= | | 2a+15=3a-18 | | (-4m^2+3n^2-5n)-[(3m^2-5n^2+2n)+(-3m^2)+4n^2]= | | -sin^2x+cos^2x= | | 2x+15+3x+5=6x-37 | | 9x+729=0 | | M=yi | | 10x-12=3x+11 | | -5x-10=q | | 2w^2+21w-180=0 | | b^-2/b^4 | | 8z^2-3z-5z^2-4z= | | 9x-2=-3 | | Z-z-z+z= | | 7x+5-5x=-11-6x |

Equations solver categories